Games of no chance 3 - Albert, Michael Henry; Nowakowski, Richard J. 1952- (Cambridge University Press, 2009)
This fascinating look at combinatorial games, that is, games not involving chance or hidden information, offers updates on standard games such as Go and Hex, on impartial games such as Chomp and Wythoff's Nim, and on aspects of games with infinitesimal values, plus analyses of the complexity of some games and puzzles and surveys on algorithmic game theory, on playing to lose, and on coping with cycles. The volume is rounded out with an up-to-date bibliography by Fraenkel and, for readers eager to get their hands dirty, a list of unsolved problems by Guy and Nowakowski. Highlights include some of Siegel's groundbreaking work on loopy games, the unveiling by Friedman and Landsberg of the use of renormalization to give very intriguing results about Chomp, and Nakamura's 'Counting Liberties in Capturing Races of Go'. Like its predecessors, this book should be on the shelf of all serious games enthusiasts
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Game theory / Congresses; Combinatorial analysis / Congresses; Konferenzschrift